Lapsi (Choerospondias axillaris (Roxb.) B.L.Burtt & A.W.Hill): A review on traditional uses, chemical constituents and biological activities - Summi Rai; Sawan Kumar Rajbanshi; Jashuda Chauhan; Pooja Shah; Eliza Acharya Siwakoti; Anima Shrestha; Prakash Poudel; Ajaya Bhattarai; Hari Prasad Devkota (Heliyon, 2025)
Lapsi (Choerospondias axillaris (Roxb.) B.L.Burtt & A.W.Hill) is an useful medicinal plant known for various bioactive compounds and diverse biological activities. The aim of this article was to comprehensively review the available information about the traditional uses, chemical constituents and biological activities of Lapsi. A comprehensive literature search was conducted using various databases, including PubMed, Scopus, Web of Science, Google Scholar, and ScienceDirect. Fruits, leaves, and bark have been extensively studied for their potential health benefits, owing to the presence of various phytochemicals such as polyphenols including flavonoids and phenolic acids, terpenoids, and essential oils. These compounds exhibited antioxidant, antimicrobial, anti-inflammatory, and anticancer properties. Additionally, the nutritional value of Lapsi fruit contributes to its popularity as a food source in traditional cuisines. In conclusion, this review explores the chemical constituents and pharmacological activities of Lapsi and highlights its importance as a multipurpose plant in various fields.